ANALISIS PRINSIP BELAJAR PADA PEMBELAJARAN MATEMATIKA SISWA KELAS X IPS II SMA NEGERI MOJOAGUNG - Iswatun Ilmiah; Jauhara Dian Nurul Iffah (Integral : Pendidikan Matematika, 2022)
This study aims to determine the application of the basic principles of learning in mathematics learning at SMA N MOJOAGUNG. The subject of this research is the teacher of class XII IPS 2 in teaching permutation material. The object of this research is students from class XII IPS 2 SMA N MOJOAGUNG Jombang. This research is a qualitative research with a descriptive approach. The instruments used to collect data are observation sheets, interview guidelines and documentation. The results of observations and interviews were analyzed based on aspects of basic principles in learning. The results of the study indicate that the application of the basic principles of learning in learning is in the good category. Keywords: Mathematics, Basic Principles of Learning.